2017
DOI: 10.1111/adb.12543
|View full text |Cite
|
Sign up to set email alerts
|

Young alcohol binge drinkers have elevated blood endotoxin, peripheral inflammation and low cortisol levels: neuropsychological correlations in women

Abstract: Alcohol binge drinking is a pattern of heavy alcohol consumption that is increasingly practiced by adolescents and young adults. Evidence indicates that alcohol binges induce peripheral inflammation and an exacerbated neuroimmune response that may participate in alcohol-induced cognitive/behavioral dysfunctions. Here, we recruited 20-year-old male and female university students who were identified as binge drinkers for at least 2 years. Compared with controls, young alcohol binge drinkers had elevated levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 50 publications
1
37
1
4
Order By: Relevance
“…Increased OEA release in the small intestine was observed in response to alcohol in vivo (Bilbao et al ., ) and to inflammation in vitro (Karwad et al ., ), suggesting a local role of OEA in regulating alcohol responses and intestinal permeability respectively. The idea that inflammation may trigger the release of OEA has been also proposed in our previous studies, in which we observed exacerbated inflammatory responses and increased plasma OEA levels in human alcohol binge drinkers (Orio et al ., ; Antón et al, ). Alcohol also induced neuroinflammation and OEA release in the frontal cortex of laboratory animals (Bilbao et al ., ; Antón et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Increased OEA release in the small intestine was observed in response to alcohol in vivo (Bilbao et al ., ) and to inflammation in vitro (Karwad et al ., ), suggesting a local role of OEA in regulating alcohol responses and intestinal permeability respectively. The idea that inflammation may trigger the release of OEA has been also proposed in our previous studies, in which we observed exacerbated inflammatory responses and increased plasma OEA levels in human alcohol binge drinkers (Orio et al ., ; Antón et al, ). Alcohol also induced neuroinflammation and OEA release in the frontal cortex of laboratory animals (Bilbao et al ., ; Antón et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…A single alcohol binge has been shown to induce a transient increase in serum endotoxin and bacterial DNA levels in healthy subjects (Bala et al ., ). We have recently reported that repeated alcohol binges increase plasma LPS in rats (Antón et al ., ) and humans (Orio et al ., ) and promote an inflammatory response that may have consequences for neurocognitive performance. However, the effects of binge drinking on intestinal barrier integrity, bacterial translocation and the mechanisms involved in gut barrier dysfunction have yet to be comprehensively investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging cross-sectional literature documents associations between alcohol use outside of the experimental context and alterations to the expected cortisol stress response profile (e.g., Orio et al, 2017). Only one study to our knowledge has prospectively examined alcohol use and biological stress system functioning.…”
Section: Introductionmentioning
confidence: 99%
“…With one exception (e.g., Jones et al, 2013), cross-sectional studies with humans have shown an attenuation of the neuroendocrine response to stress (i.e., a decrease in levels across an acute stressor) among adults who report binge drinking or other forms of heavy alcohol use (Lovallo et al, 2000;Orio et al, 2017). Atypical patterns of cortisol reactivity, such as a blunted response, have been associated with a wide range of physical and mental health problems (for a review, see Phillips et al, 2013).…”
Section: Introductionmentioning
confidence: 99%